Framework de valoração de ativos intangíveis : uma proposta para a determinação do valor de referência de patentes na UFMT - Fochesatto, Danilo Botelho Lannes (2020)
The exploration of the technological-scientific potential of universities is a recent reality that enables the generation of economic returns for these institutions. Because of this, it is important that such research centers are able to negotiate their intangible assets. However, to do so, it is necessary to determine an economic reference value for the assets of their portfolios. This is, notedly, a complex and multidisciplinary task, since the economic value of a technology is affected by several technical and non-technical factors. In light of this, the present research aimed to propose a framework capable of enabling the economic valuation of patents at the Federal University of Mato Grosso – UFMT. To achieve this goal, systematic review was used, in august 2019, in order to identify and analyze the most widespread available technology valuation methodologies. In especific, this research also carried out the identification and mapping of the technology transfer process at UFMT, using Business Process Modeling Notation (BPMN). Seeking to describe, in practice, the use of technology valuation models and their suitability for concrete cases, three patents from the UFMT portfolio were valued in with the help of the proposed framework. It was found during the research that there is still a need for further studies related to the theme, since the absence of models for valuing technologies and intangibles is still quite common, notably in public research institutions. On the other hand, it was found that the methodologies for valuing technologies available in the literature can provide good contributions to the patent valuation process, among which stand out speed and verifiability. It was also found that certain valuation methodologies can only be applied after a certain degree of technology maturity, and, in addition, the need for market intelligence studies, especially in the regional context of Mato Grosso, became clear.